2007
DOI: 10.1194/jlr.m700113-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA for apolipoprotein M reveals a strong correlation to total cholesterol in human plasma

Abstract: Apolipoprotein M (apoM) is a 188 amino acid, 25 kDa protein belonging to the lipocalin protein superfamily. Although predominantly associated with high density lipoprotein, apoM is found in all major lipoprotein classes. To facilitate clinical studies of apoM, we have developed a sandwich ELISA for the measurement of apoM in human plasma. This method has been used to investigate normal apoM variation and to establish reference values for healthy individuals through the measurement of 598 samples from the Nordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 32 publications
7
94
0
Order By: Relevance
“…In agreement with these results, we also found significantly lower levels of ApoM in participants with T2DM compared to participants with NGT; however, the difference was present only in Swedes but not in Iraqis. The mean plasma ApoM concentration in healthy individuals has been shown to be 0.9 µM [24]. In concurrence with these results, we found approximately the same levels of ApoM in Swedish participants with NGT; however, Iraqi participants with NGT had significantly lower levels of ApoM.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In agreement with these results, we also found significantly lower levels of ApoM in participants with T2DM compared to participants with NGT; however, the difference was present only in Swedes but not in Iraqis. The mean plasma ApoM concentration in healthy individuals has been shown to be 0.9 µM [24]. In concurrence with these results, we found approximately the same levels of ApoM in Swedish participants with NGT; however, Iraqi participants with NGT had significantly lower levels of ApoM.…”
Section: Resultssupporting
confidence: 79%
“…Furthermore, recent evidence suggests that HDL may directly contribute to the pathogenesis of T2DM through its ability to enhance pancreatic β-cell function and glucose uptake in skeletal muscles [27]. HDL levels are known to strongly correlate with ApoM [24] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoM is an apolipoprotein found mainly in HDL (Axler et al 2007) which possesses an eight stranded antiparallel beta-barrel lipocalin fold and a hydrophobic pocket that ensures binding of small hydrophobic molecules, primarily sphingosine-1-phosphate (S1P) (Ahnstrom et al 2007;Christoffersen et al 2011). ApoM reveals 19 % homology with apoD, another apolipoprotein member of the lipocalin family (Sevvana et al 2009), and is synthesised in the liver and kidney.…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…Studies in humans and in mice overexpressing or lacking apoM have shown a positive association between plasma apoM levels and total as well as HDL and LDL cholesterol concentrations (21)(22)(23). Wolfrum et al (24) demonstrated that the lack of apoM expression in transcription factor-1␣/hepatocyte nuclear factor-1␣ (TCF-1␣/HNF-1␣) knock-out mice or in apoM small interfering RNA-injected mice leads to formation of larger size HDL1 particles and the disappearance of pre-␤-HDL particles in plasma suggesting that apoM may play a role in HDL remodeling, particularly with regard to metabolism of pre-␤-HDL.…”
mentioning
confidence: 99%